Lipoic Acid for Rheumatological Diseases: A Systematic Review - Freire de Carvalho, Jozélio; Ferreira da Silva, Thiago (Cerrahpaşa Medical Journal, 2024)
Abstract Lipoic acid (LA) is a potent antioxidant and has been tested in a few rheumatic diseases. To review the use of LA in rheumatic diseases. PubMed/ MEDLINE, EMBASE, and Scielo databases were screened for articles on LA and rheumatic diseases between 1966 and May 2023. Four articles were found, including 177 patients. The investigated diseases were fibromyalgia (FM) (n = 2) and rheumatoid arthritis (RA) (n = 2). Age varied from 36.09 ± 8.77 to 57 (25-74) years old, and the female gender ranged from 81% to 100%. LA dosage ranged from 300 mg to 1663mg/day. Concerning outcomes, three-fourths of the article did not observe any difference when LA was compared to placebo. On the contrary, in one study, a significant decrease in pain and an improvement in fibromyalgia impact questionnaire (FIQ) and Fatigue Severity Scale (FSS) scores were seen in the LA-supplemented group. Lipoic acid is a potent antioxidant, and it was a safe therapy for FM and RA, although in only one study, in FM subjects, a positive result was found. Cite this article as: Freire de Carvalho J, Ferreira da Silva T. Lipoic acid for rheumatological diseases: a systematic review. Cerrahpaşa Med J. 2024;48(3):302-305.